Antitumor properties of Ganoderma lucidum polysaccharides and terpenoids - Camargo, Marcela R. [UNESP]; Kaneno, Ramon [UNESP] (My University, 2011)
Ganoderma lucidum is an edible medicinal mushroom with immunomodulatory and antitumor properties, which are mainly attributed to polysaccharides and triterpenes that can be isolated from mycelia, fruiting bodies and spores. G. lucidum has been us d in a powdered form, as a medicinal beverage and a nutraceutical food (usually dried). In the present review we report some historical facts and the experimental evidence that polysaccharides and triterpenes obtained from this mushroom present potential antitumor activity. Direct effects on tumor cells include induction of apoptosis and interference in the cell cycle, whereas indirect effects are based on the modulation of immune response, usually impaired by cancer cells. Data indicate that G. lucidum can be used as a complementary tool for treatment of cancer patients. © by São Paulo State University.
Keywords: Immunomodulation; Mushroom; Polysaccharides; Triterpenes; Tumor; caspase; gamma interferon; ganoderic acid; Ganoderma lucidum extract; Ganoderma lucidum polysaccharide; ganodermanontriol; interleukin 10; interleukin 12; polysaccharide; protein Bax; protein bcl 2; protein Bid; reactive oxygen metabolite; terpenoid; triterpenoid; tumor necrosis factor alpha; unclassified drug; antineoplastic activity; apoptosis; cell cycle arrest; cell proliferation; colon cancer; cytokine production; cytotoxicity; dendritic cell; drug isolation; Ganoderma lucidum; human; immunomodulation; innate immunity; macrophage; natural killer cell; nonhuman; oxidative stress; spleen lymphocyte; T lymphocyte; Th1 cell; tumor cell destruction; Basidiomycota